The Influence of Organizational Support on Employee Performance through Employee Engagement at PT Kereta Api. - Wiryawan, Raditya (JURNAL STUDI MANAJEMEN ORGANISASI, 2025)
This study aims to analyze the effect of Perceived Organizational Support on Employee Performance with Employee Engagement as an intervening variable on employees of PT Kereta Api Pariwisata. Perceived organizational support is one of the important factors that affect employee performance through employee involvement in carrying out tasks.This study uses a quantitative method with the Partial Least Squares approach involving 149 employees as respondents Employee Performance. Employee Performance. This finding confirms that good Perceived organizational support will increase employee engagement, which ultimately has an impact on improving employee performance. The implications of this study provide recommendations for company management to continue to improve perceived organizational support in terms of employee welfare and two-way communication policies to strengthen employee engagement and performance.